2018
DOI: 10.1007/s00264-018-4185-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction after total knee arthroplasty is better in patients with pre-operative complete joint space collapse

Abstract: Aim of the study To determine if pre-operative radiologic minimal joint space width (mJSW) is related to the outcome of total knee arthroplasty (TKA) (primary hypothesis). Likewise, the aim was to test if pre-operative mJSW is related to prosthesis survival (secondary hypothesis). Methods A retrospective comparative analysis was performed. Group 1 was comprised of patients with pre-operative mJSW 0–1 mm. Group 2 were patients with pre-operative mJSW ≥ 2 mm. The clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…It has been mentioned in some studies that KL score should not be the preferred tool for assessing OA severity [9,39], as some studies question the classification's inter-rater and intra-rater reliability [29,40] and the use of differing descriptions of the grading system [29] makes it difficult to compare findings between studies. A study comparing 3 different X-ray scoring methods of knee OA concluded that joint space width evaluation on semiflexed views might be the preferred method to evaluate the severity of knee OA [39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been mentioned in some studies that KL score should not be the preferred tool for assessing OA severity [9,39], as some studies question the classification's inter-rater and intra-rater reliability [29,40] and the use of differing descriptions of the grading system [29] makes it difficult to compare findings between studies. A study comparing 3 different X-ray scoring methods of knee OA concluded that joint space width evaluation on semiflexed views might be the preferred method to evaluate the severity of knee OA [39].…”
Section: Discussionmentioning
confidence: 99%
“…In a long-term study on quality of life and costs in a U.S. cohort of patients followed up to eight years, quality of life improvements and cost benefits associated with surgical intervention can only be appreciated in the highest risk patients and support the necessity for early medical management [23]. Patients with preoperative complete joint space collapse (0 to 1 mm mJSW) achieve a significantly better WOMAC result from TKA than those with a mJSW equal to or greater than 2 mm [24].…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroscopy (TKA) is a common surgical intervention, in the USA, more than 600,000 patients receive TKA every year [4]. With the continuous development and improvement of surgical techniques and implants, long-term postoperative patient satisfaction can reach 80% and the survival rate of the prosthesis can exceed 95% [5][6][7].…”
Section: Introductionmentioning
confidence: 99%